The Role of Guidance and Counseling Teachers in Improving Student Learning Success - Reginald Putera Hernawan; Imam Tabroni; Zhang Wei; Shanshan Xu (Journal Emerging Technologies in Education, 2023)
Background. This study was to determine the role of guidance and counseling teachers in improving student learning success at SMA Negeri 1 Cibatu Purwakarta. Purpose. The method used in this research is descriptive qualitative manifold generate descriptive data to describe the behavior of the subject under study. Method. Then the presence of investigators in this study serves as primary research tool. Sources of data in this study are primary data obtained through observation and interview respondents. Results. And secondary data documentation Master's programs of guidance and counseling. Data collection techniques in this study using the method of observation, interviews, and documentation. And next data analysis in this study using qualitative data analysis. Conclusion. The results showed that the models of guidance and counseling program in SMA Negeri 1 Cibatu form their Intensification Program for class XII, intensification program contains material National Examinations and Pathways to college, learning programs in addition to class 10 and 11 to face the Final Exams Semester in order to satisfy student achievement, educational exhibits, and extracurricular programs in SMA Negeri 1 Cibatu